Azar, libertad y responsabilidad : aportes para una práctica psicológica (2013)
ABSTRACT: This article offers a look at responsibility from the concepts of fortuity and freedom, which we consider fundamental in the argument that a subject has the option to choose despite his determinations. Fortuitous is understood as unpredictable behavior of certain events, given their lack of regularity. We believe that any situation is driven by both, deterministic and random influences. Meanwhile freedom is possibility of choice. Responsibility is assumed to be a consequence of fortuity and freedom, defined as “the response that fits the self-being” (Ramírez, 2012, p. 45). As a consequence, we suggest that psychology, in any of its fields, may create effects of accountability on the subject, by the subject itself and by its environment, considering the ways in which a human being may respond in a given situation: elementary, primary or secondary. It should be mentioned that the secondary response characterizes ethical responsibility, promoted by psychological practice based on an analytical attitude.